Comparative mode of action of some terpene compounds against octopamine receptor and acetyl cholinesterase of mosquito and human system by the help of homology modeling and Docking studies - Bulbuli Khanikor, Pratap Parida, R.N.S. Yadav and Dipsikha Bora (Journal of Applied Pharmaceutical Science, 2013)
Mosquitoes are vectors of many diseases like malaria, encephalitis, dengue, filaria, yellow fever etc. and thus possess severe threat to public health. Essential oils of some aromatic plants and many pure terpene compounds have been reported effective against different strains of mosquitoes by many authors. In the present investigation, five reported terpene compounds namely eugenol, geraniol, coumarin, eucalyptol and carvacrol were allowed to dock against octopamine receptor and acetyl cholinesterase protein models of Aedes aegypti and Homo sapiens to evaluate their comparative efficacy in terms of docking performance. All the compounds were found to dock with both the protein models of the two animal systems while some of them were found to better perform against the protein models of A.aegypti than the protein models of H.sapiens which can further be explored in mosquito control programme as a comparatively safe compound(s). The results are discussed on the basis of energy value. 3D structures of proteins were modeled using Modeller9v8. The structures assessment were established using the Procheck, WhatCheck and WhatIF server of Swiss Model Workspace. Ligands were prepared using the Commercial Software Exome HorizonTM.
Keywords: Eugenol, geraniol, coumarin, eucalyptol, carvacrol